Kajian Model dan Prototipe Schema Matching (Studi untuk Menemukan Peluang Pengembangan Model dan Prototipe Baru) - Sutanta, Edhy (2015)
Schema matching is critical problem within many applications to integration of data / information, to achieve interoperability, and other cases caused by schematic heterogeneity.Models and the schema matching methods evolved from manual way on a specific domain, leading to a new models and methods that are semi-automatic and more general, so it is able to effectively direct the user within generate a mapping among elements of two the schema or ontologies better. This paper is a summary of literature review on research and publication on models, methods, and prototypes on schema matching within the last 25 years to describe the progress of and research opportunities on new models, methods, and prototypes.